1998
DOI: 10.1177/00220345980770121001
|View full text |Cite
|
Sign up to set email alerts
|

Residual Monomer/Additive Release and Variability in Cytotoxicity of Light-curing Glass-ionomer Cements and Compomers

Abstract: In previous studies, light-cured glass-ionomer cements have been shown to evoke cytotoxic reactions. It was the purpose of this investigation (a) to determine the nature of the ingredients released into an aqueous medium from 2 light-cured glass-ionomer cements (GICs) and 3 compomers; (b) to evaluate the cytotoxicity of these extracts; and (c) to correlate the extent of the cytotoxic effects with eluted substances. Specimens of 2 light-cured GICs and 3 compomers were prepared and extracted in distilled water o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 26 publications
5
168
0
3
Order By: Relevance
“…An inadequate polymerization affects biocompatibility due to the release of monomers that may damage cells in oral tissues (21). This would argue for higher CQ/amine concentrations to maximize cure.…”
Section: Discussionmentioning
confidence: 99%
“…An inadequate polymerization affects biocompatibility due to the release of monomers that may damage cells in oral tissues (21). This would argue for higher CQ/amine concentrations to maximize cure.…”
Section: Discussionmentioning
confidence: 99%
“…In general, CGPCs do not pose an acute systemic risk or chronic toxic behavior; however, it is important to assess their systemic toxicity prior to their market launch. A number of studies [100][101][102][103][104][105] intensively investigated the cytotoxicity of CGPCs. It was consistently illustrated that the cytotoxic behavior of CGPCs depends on their setting reaction.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Major monomers and co-monomers have been identified as the cytotoxic components of the organic matrix of resin composite materials, and a relationship between the structural and biological activities of monomers has been reported 14,15) . Two-hydroxyethyl methacrylate (HEMA), triethyleneglycol dimethacrylate (TEGDMA), bisphenol A-glycidyl-methacrylate (Bis-GMA), and urethane dimethacrylate (UDMA) are common constituents of restorative materials and have been identified in aqueous extracts from cured resin restoratives 16,17) . Several in vitro studies have shown that HEMA and Evaluation of cytotoxic effects of six self-etching adhesives with direct and indirect contact tests TEGDMA have cytotoxic potentials 18,19) to a lesser degree than the more hydrophobic monomers Bis-GMA or UDMA 9) .…”
Section: Introductionmentioning
confidence: 99%